1983
DOI: 10.1515/znc-1983-5-616
|View full text |Cite
|
Sign up to set email alerts
|

A Cysteine Desulfhydrase Specific for ᴅ-Cysteine from the Green Alga Chlorella fusca

Abstract: A cysteine desulfhydrase was purified 110-fold from the green alga Chlorella using conven­tional techniques. The isolated cysteine desulfhydrase was specific for ᴅ-cysteine having no activity towards ʟ-cysteine. ᴅ- and ʟ-cysteine desulfhydrase activities can be separated using DEAE-cellulose chromatography techniques. The isoelectric point of this enzyme was deter­mined to be around a pH of 4.5 using a chromatofocussing column. The pH-optimum for the ᴅ-cysteine desulfhydrase was found to be in the range of 8.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In several organisms, D-cysteine desulfhydrase activity (EC 4.4.1.15), decomposing D-cysteine into pyruvate, H 2 S, and ammonium, has been measured (Nagasawa et al, 1985(Nagasawa et al, , 1988. Similar activity was detected in several plant species, such as Spinacia oleracea, Chlorella fusca, Cucurbita pepo, Cucumis sativus and in suspension cultures of Nicotiana tabacum (Schmidt, 1982;Schmidt and Erdle, 1983;Rennenberg, 1983;Rennenberg et al, 1987). In all publications cited, the D-cysteine desulfhydrase activity could be clearly separated from L-cysteine desulfhydrase activity, by demonstrating different pH optima for enzyme activity (Schmidt, 1982), different sensitivity to inhibitors (Rennenberg et al, 1987), and different localizations in the cell (Rennenberg et al, 1987).…”
Section: Identification and Characterization Of Cysteine Desulfhydrasmentioning
confidence: 86%
“…In several organisms, D-cysteine desulfhydrase activity (EC 4.4.1.15), decomposing D-cysteine into pyruvate, H 2 S, and ammonium, has been measured (Nagasawa et al, 1985(Nagasawa et al, , 1988. Similar activity was detected in several plant species, such as Spinacia oleracea, Chlorella fusca, Cucurbita pepo, Cucumis sativus and in suspension cultures of Nicotiana tabacum (Schmidt, 1982;Schmidt and Erdle, 1983;Rennenberg, 1983;Rennenberg et al, 1987). In all publications cited, the D-cysteine desulfhydrase activity could be clearly separated from L-cysteine desulfhydrase activity, by demonstrating different pH optima for enzyme activity (Schmidt, 1982), different sensitivity to inhibitors (Rennenberg et al, 1987), and different localizations in the cell (Rennenberg et al, 1987).…”
Section: Identification and Characterization Of Cysteine Desulfhydrasmentioning
confidence: 86%
“…Green Alga and Plant D-Cysteine Desulfhydrases-D-Cysteine desulfhydrase activity was early identified in the green alga C. fusca and in the plant S. oleracea (2,3) Cyanobacteria can also utilize D-cysteine as their sole sulfur source. From this property, it was suggested that these bacteria contain a D-cysteine desulfhydrase (3).…”
Section: Comparison Of E Coli Desulfhydrase With Related Enzymesmentioning
confidence: 99%
“…The Escherichia coli d ‐CDes (EC 4.1.99.4) is capable of catalysing the transformation of d ‐cysteine into pyruvate, H 2 S, and NH 3 [9,10]. A similar activity was detected in several plant species, such as Spinacia oleracea , Chlorella fusca , Cucurbita pepo , Cucumis sativus and in suspension cultures of Nicotiana tabacum [11–14]. In all publications cited, the d ‐CDes activity could be clearly separated from l ‐CDes activity by demonstrating different pH optima for the enzyme activity [11], different sensitivity to inhibitors [14], and different localization in the cell [14].…”
mentioning
confidence: 98%